Basement reactivation and structural inheritance in the Jurassic to Neogene evolution of the North Patagonian Andes (Argentina). - Peltzer, Sofía (2024)
Fil: Peltzer, Sofía. Universidad de Buenos Aires, Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires (IGEBA), Intendente Güiralde s 2160, C1428EHA, Buenos Aires, Argentina